2021
DOI: 10.3389/fcimb.2021.680127
|View full text |Cite
|
Sign up to set email alerts
|

Artemether, Artesunate, Arteannuin B, Echinatin, Licochalcone B and Andrographolide Effectively Inhibit SARS-CoV-2 and Related Viruses In Vitro

Abstract: Since the first reported case caused by the novel coronavirus SARS-CoV-2 infection in Wuhan, COVID-19 has caused serious deaths and an ongoing global pandemic, and it is still raging in more than 200 countries and regions around the world and many new variants have appeared in the process of continuous transmission. In the early stage of the epidemic prevention and control and clinical treatment, traditional Chinese medicine played a huge role in China. Here, we screened out six monomer compounds, including ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
(55 reference statements)
1
27
0
Order By: Relevance
“…Artemether, artesunate and, arteannuin B remarkably reduced pangolin coronavirus GX_P2V infection (artemether (EC 50 = 3.701 µM, CC 50 > 200 µM, SI > 54.04), artesunate (EC 50 = 10.10 µM, CC 50 = 127.3 µM, SI = 12.60), and arteannuin B (EC 50 = 8.838 µM, CC 50 = 116.9 µM, SI = 13.23)) [193]. The time-of-addition assay and Western blot showed that artemether functioned at both entry and post-entry stages, whereas the other two compounds functioned at the post-entry stage.…”
Section: Inhibition Potential Of Artemisia Constituents Including Art...mentioning
confidence: 98%
“…Artemether, artesunate and, arteannuin B remarkably reduced pangolin coronavirus GX_P2V infection (artemether (EC 50 = 3.701 µM, CC 50 > 200 µM, SI > 54.04), artesunate (EC 50 = 10.10 µM, CC 50 = 127.3 µM, SI = 12.60), and arteannuin B (EC 50 = 8.838 µM, CC 50 = 116.9 µM, SI = 13.23)) [193]. The time-of-addition assay and Western blot showed that artemether functioned at both entry and post-entry stages, whereas the other two compounds functioned at the post-entry stage.…”
Section: Inhibition Potential Of Artemisia Constituents Including Art...mentioning
confidence: 98%
“…Vaccines and antiviral drugs are important strategies to prevent and treat COVID-19. A variety of drugs with different mechanisms of action were evaluated in preclinical studies or clinical trials ( 2 , 3 ). The main drug groups include inhibitors of virus entry into cells (chloroquine, hydroxychloroquine, camostat mesylate, human recombinant soluble ACE2, neutralizing antibodies, nanobodies, miniproteins, convalescent plasma, umifenovir, nitazoxanide, whey protein and lactoferrin) ( 4 15 ), inhibitors of SARS-CoV-2 RNA (remdesivir, ribavirin, favipiravir, molnupiravir, and AT-527) ( 16 20 ), inhibitors of viral 3CL proteases (lopinavir/ritonavir, PF-07321332, PF-07304814, GC376, and GS-621763) ( 21 25 ), inhibitors of host factors essential for virus infection (plitidepsin, fluvoxamine, and ivermectin) ( 26 28 ), immunomodulators (dexamethasone, tocilizumab, sarilumab, bevacizumab, eculizumab, and interferons) ( 29 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, drugs ( 53 , 75 , 76 ) and microorganisms ( 77 , 78 ) combined with LF can better inhibit the activity of SARS-CoV-2. In the future, the effect of other drugs which are capable of inhibiting SARS-CoV-2, such as artemether ( 110 ), artesunate ( 110 ), cepharanthine ( 111 ), and molnupiravir ( 112 , 113 ), combined with human milk ingredients against SARS-CoV-2 can also be further investigated.…”
Section: Discussionmentioning
confidence: 99%